Thermal analysis of a Trombe wall in various climatic conditions: An experimental study. (1st September 2022) - Mokni, Ameni; Lashin, Ashraf; Ammar, Marwa; Mhiri, Hatem
Highlights: The radiative exchanges are predominant compared to the convective exchanges. That thermo circulation is strongly related to the sunshine hours and the intensity of radiation. The Trombe wall can meet 80% of the heating needs of the room during a sunny day with low wind. The Trombe wall can meet 42% in the case of a sunny day with fairly strong wind. The Trombe wall can meet 37% of the heat needed during a day with scattered or low-density clouds. Abstract: The soaring energy prices incite us to value any available and free energy source. This paper is a contribution to improving the integration of passive solar systems in buildings. It consists in an experimental study of a Trombe wall in the Abha region of Saudi Arabia under real climatic conditions. The recorded experimental results are used to evaluate the solar gains collected by a room during the heating season. The experimental results combined with predictions based on thermal analysis are used to evaluate the different heat exchange coefficients, the thermo-circulation in the gap, and the total amount of heat captured during the sunshine hours. The influence of climatic factors such as wind and cloud cover has been analysed. The results show that the fraction of solar radiation transmitted inside is lower than losses to the outside, radiative exchanges are more important than convective ones. The quantity of heat collected during the days of experimentation varies according to climatic conditions. The Trombe wall can meet 80% of the heating needs of the room during a sunny day with low wind, 42% in the case of a sunny day with strong wind, and 37% during a day with scattered or low-density clouds. Even in the case of heavy cloud cover, the Trombe wall can provide 14% of heating needs.